Monocrystal cobaltosic oxide and preparation method thereof, lithium cobalt oxide positive electrode material and battery

Single-crystal Cobalt tetroxide is prepared by grinding and spray drying of cobalt chloride and carbonate in lithium cobalt oxide positive electrode material, and the problems of cumbersome processes and high production costs in the prior art are solved, and high-performance single-crystal Cobalt tetroxide are achieved Preparation to meet the demand for high voltage, high compaction and high cycle performance of lithium cobalt oxide cathode materials.

CN119320990APending Publication Date: 2025-01-17GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411415233.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing technology is complicated in the preparation of single-crystal cobalt tetroxide, and the production cost is high, making it difficult to meet the demand for high voltage, high compaction and high cycle performance of lithium cobalt oxide positive electrode materials. There are high pores inside the polycrystalline small particle raw materials, which affects the Material properties.

Method used

Cobalt chloride and carbonate are dispersed in the dispersant for grinding, and then the premixed material is formed and the single crystal cobalt tetroxide is prepared by spray drying. The crystal surface growth is controlled in combination with the calcination process to obtain small particle size, narrow particle size distribution, and solid powder Single crystal cobalt tetroxide with high density and large specific surface area.

Benefits of technology

It realizes simple and economical industrial production of single-crystal cobalt tetroxide, improves the compaction density and rate performance of lithium cobalt oxide positive electrode materials, and meets the needs of high voltage, high compaction and high cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320990A_ABST
    Figure CN119320990A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and provides single-crystal cobaltosic oxide and a preparation method thereof, a lithium cobalt oxide positive electrode material and a battery, the (111) crystal face diffraction peak intensity I (111) and (400) crystal face diffraction peak intensity I (400) of the single-crystal cobaltosic oxide meet the condition that I (111) / I (400) is greater than or equal to 1.10 and less than or equal to 1.30, the preparation method has the advantages of small particle size, narrow particle size distribution, high particle size uniformity, high powder tap density and large specific surface area. The preparation method comprises the following steps: carrying out wet grinding on cobalt chloride and carbonate, and further carrying out spray drying to prepare a precursor of cobaltosic oxide; the refining degree and the reaction activity of particles in the slurry are increased by using a grinding method; by means of spray drying, particles are not agglomerated in the drying process, uniformity and dispersity are kept, a finer and more uniform precursor is obtained, and ion diffusion in the high-temperature calcination process is facilitated; meanwhile, chloride ions are adsorbed on the crystal face (111), growth of the crystal face (111) is limited, growth of the crystal face (400) is promoted, cobaltosic oxide meeting the requirement that I (111) / I (400) is larger than or equal to 1.10 and smaller than or equal to 1.30 is prepared, the technological method is simple, and industrial production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to single-crystal cobalt oxide and a preparation method thereof, a lithium cobalt oxide positive electrode material and a battery. Background Art

[0002] With the rapid development of the electronic communications field, better opportunities have been created for the development of the lithium-ion battery industry. Correspondingly, the demand for lithium cobalt oxide, the cathode material of lithium-ion batteries, and its raw material cobalt tetroxide have also increased significantly. As the precursor material of lithium cobalt oxide cathode, the material properties of cobalt tetroxide greatly affect the performance of lithium cobalt oxide.

[0003] Lithium cobalt oxide is developing in the direction of high voltage, high compaction and high cycle performance, and the requirements for the raw material cobalt oxide are getting higher and higher. The morphology of cobalt oxide has a certain influence on the morphology of lithium cobalt oxide. At present, most of the positive electrode materials of lithium cobalt oxide are based on polycrystalline small-particle cobalt oxide of conventional secondary spherical particles, but there are high pores inside the polycrystalline small-particle raw materials. Single-crystal small-particle cobalt oxide products can improve the compaction density and rate performance of lithium cobalt oxide, so the market demand for single-crystal small-particle Co3O4 is gradually becoming prominent. Nowadays, research on how to prepare single-crystal small-particle cobalt oxide has gradually become a hot topic.

[0004] The prior art generally adopts a liquid phase precipitation method to prepare cobalt tetroxide, but this method has complicated procedures and high production costs, and is therefore not conducive to industrial production.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention includes providing a single crystal cobalt oxide and a preparation method thereof, a lithium cobalt oxide positive electrode material and a battery. The first aspect is to provide a single crystal cobalt oxide with a small particle size, a narrow particle size distribution, a high powder tap density and a large specific surface area; the second aspect is to provide a simple process method that is conducive to the industrial production of cobalt oxide.

[0007] In order to achieve the above-mentioned object, the present invention provides a single crystal cobalt oxide in a first aspect, comprising: in the X-ray diffraction pattern of the single crystal cobalt oxide, the (111) crystal plane diffraction peak intensity I(111) and the (400) crystal plane diffraction peak intensity I(400) satisfy: 1.10≤I(111) / I(400)≤1.30.

[0008] In some embodiments of the present invention, the single crystal cobalt oxide comprises at least one of the following features 1 to 6: Feature 1: The single crystal cobalt tetraoxide D v50 3.0-5.0um; Feature 2: The single crystal cobalt tetraoxide Dv90 4.0-9.0um; Feature 3: The tap density of the single crystal cobalt oxide is 2.0-3.0 g / ml; Feature 4: The specific surface area of ​​the single crystal cobalt oxide is 0.6-0.8m2 / g; Feature 5: The span of the single crystal cobalt oxide is 1.0-1.3; Feature 6: The percentage of particles of the single-crystal cobalt tetroxide that are octahedral in shape is 1%-10%, and the octahedron refers to a polyhedron with eight faces and six vertices.

[0009] In a second aspect, the present invention provides a method for preparing single-crystal cobalt oxide, the method comprising the following steps: dispersing cobalt chloride and carbonate in a dispersant to obtain a premix; The premix is ​​ground to obtain a slurry; The slurry is spray-dried to obtain a precursor; The precursor is calcined and crushed to obtain single crystal cobalt tetroxide.

[0010] In some embodiments of the present invention, the molar concentration ratio of the cobalt chloride to the carbonate is 1:2-3; And / or, the mass ratio of the total mass of the cobalt chloride and the carbonate to the mass of water is 10%-30%.

[0011] In some embodiments of the present invention, the dispersant includes at least one of water and ethanol; And / or, the grinding method includes at least one of vertical ball milling, ultrasonic grinding and high-speed dispersion.

[0012] In some embodiments of the present invention, when the grinding method is ball milling, the mass ratio of balls to materials in the ball mill is 8-10:1; And / or, the rotation speed of the ball mill is 800-1000 rpm / min, and the time is 1-2h.

[0013] In some embodiments of the present invention, during the spray drying, the feed flow rate is 2-5 L / h; and / or, the atomization frequency is 380-400 Hz; and / or, the induced air frequency is 35-40 Hz; And / or, the atomizing nozzle is a two-fluid nozzle, and the ratio of the air flow speed to the feed speed is controlled to be 0.1-10.

[0014] In some embodiments of the present invention, the calcination process temperature is 600-800°C.

[0015] The present invention provides a lithium cobalt oxide positive electrode material in a third aspect. The lithium cobalt oxide is obtained by mixing cobalt trioxide and a lithium source and then calcining.

[0016] The present invention provides a battery in a fourth aspect, the battery comprising a positive electrode sheet, and the positive electrode sheet comprises the lithium cobalt oxide positive electrode material.

[0017] The beneficial effects of the present invention include: The single crystal cobalt tetroxide provided by the present invention has a (111) crystal plane diffraction peak intensity I(111) and a (400) crystal plane diffraction peak intensity I(400) satisfying the following conditions: 1.10≤I(111) / I(400)≤1.30, thereby obtaining single crystal cobalt tetroxide with small particle size, narrow particle size distribution, high particle size uniformity, high powder tap density and large specific surface area.

[0018] The invention provides a method for preparing single crystal cobalt tetroxide. Cobalt chloride and carbonate are wet-grinded and then spray-dried to obtain a cobalt tetroxide precursor. The grinding method is used to increase the refinement degree and reaction activity of particles in the slurry. The spray drying prevents the particles from agglomerating during the drying process, maintains uniformity and dispersibility, and obtains a finer and more uniform precursor, which is beneficial to ion diffusion during high-temperature calcination. At the same time, chloride ions are adsorbed on the (111) crystal plane, restricting the growth of the (111) plane and promoting the growth of the (400) crystal plane, so as to obtain cobalt tetroxide that meets 1.10≤I(111) / I(400)≤1.30. In addition, the number percentage of particles that meet the single crystal cobalt tetroxide shape of octahedron obtained by combining the grinding method and the spray drying method is 1%-10%, and the process method is simple and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 A process flow chart of the preparation method of single crystal cobalt tetroxide provided in Example 1; Figure 2 a and Figure 2 b is the SEM image of the precursor prepared in Example 1 at different magnifications; Figure 3 The XRD pattern of the precursor prepared in Example 1; Figure 4 a and Figure 4 b is the SEM images of the single crystal cobalt oxide prepared in Example 1 at different magnifications; Figure 5 The XRD pattern of the single crystal cobalt oxide prepared in Example 1; Figure 6 a and Figure 6 b is the SEM image of the precursor prepared in Comparative Example 1 at different magnifications; Figure 7 The XRD pattern of the precursor prepared in Comparative Example 1; Figure 8 a and Figure 8 b is the SEM images of the single crystal cobalt oxide prepared in Comparative Example 1 at different magnifications; Fig. 9 The XRD pattern of the single crystal cobalt oxide prepared in Comparative Example 1; Fig.10 a and Fig.10 b is the SEM image of the precursor prepared in Comparative Example 2 at different magnifications; Fig.11 This is the XRD pattern of the precursor prepared in Comparative Example 2; Fig.12 a and Fig.12 b is the SEM images of the single crystal cobalt oxide prepared in Comparative Example 2 at different magnifications; Fig.13 This is the XRD spectrum of single crystal cobalt oxide prepared in Comparative Example 2. DETAILED DESCRIPTION

[0021] Hereinafter, a single crystal cobalt oxide and its preparation method, a lithium cobalt oxide positive electrode material and a battery of the present invention are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0022] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. In particular, "()", ")", "[" and "]" represent intervals, where "(" or ")" represents an open interval, that is, the endpoint values ​​of the interval are not included; "[" and "]" represent a closed interval, that is, the endpoints within the interval are included. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range.

[0023] Specifically, for example, if the ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that the ranges of 60-110 and 80-120 are also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been fully listed in this article, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a certain parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. If (10, 20) is listed, it is understood as any value between 10 and 20, excluding 10 and 20; (10, 20] is understood as any value between 10 and 20, excluding 10 but including 20.

[0024] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0025] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0026] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0027] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0028] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0029] A first aspect of the present invention provides a single crystal cobalt oxide, wherein in an X-ray diffraction pattern of the single crystal cobalt oxide, the (111) crystal plane diffraction peak intensity I(111) and the (400) crystal plane diffraction peak intensity I(400) satisfy: 1.10≤I(111) / I(400)≤1.30.

[0030] The single crystal cobalt oxide provided by the present invention is a single crystal with a polyhedral morphology and a typical spinel structure. The relative growth rates of the (111) crystal plane and the (400) crystal plane of the crystal will affect its morphology, and the morphology of the cobalt oxide and the dominant orientation of the crystal plane will affect the compressive properties of lithium cobalt oxide and the diffusion properties of lithium ions, thereby affecting the electrochemical properties of lithium cobalt oxide. The cobalt oxide provided by the present invention satisfies 1.10≤I(111) / I(400)≤1.30, and has the advantages of small particle size, narrow particle size distribution, high powder tap density and large specific surface area.

[0031] In some embodiments, the single crystal cobalt oxide comprises at least one of the following features 1 to 6: Feature 1: The single crystal cobalt tetraoxide D v50 3.0-5.0um; Feature 2: The single crystal cobalt tetraoxide D v90 4.0-9.0um; Feature 3: The tap density of the single crystal cobalt oxide is 2.0-3.0 g / ml; Feature 4: The specific surface area of ​​the single crystal cobalt oxide is 0.6-0.8m2 / g; Feature 5: The span of the single crystal cobalt oxide is 1.0-1.3; Feature 6: The percentage of particles of the single-crystal cobalt tetroxide that are octahedral in shape is 1%-10%, and the octahedron refers to a polyhedron with eight faces and six vertices.

[0032] The span represents the width of the particle size distribution, and the span value satisfies: span= The larger the span value, the wider the particle size distribution, and the smaller the span value, the narrower the particle size distribution.

[0033] In some embodiments, the number of particles having an octahedral shape in the single-crystal cobalt oxide powder is calculated as follows: By analyzing the image of the single crystal cobalt oxide powder such as SEM, the powder particles in the image are counted using image processing software; one counted particle is a primary particle with a maximum diameter ≥ 0.1 μm; the number of octahedral morphology accounts for the number of all counted particles by the following formula: Formula =

[0034] In a second aspect, the present invention provides a method for preparing single-crystal cobalt oxide, the method comprising the following steps: Cobalt chloride and carbonate are dispersed in a dispersant to obtain a premix; The premix is ​​ground to obtain a slurry; The slurry is spray-dried to obtain a precursor; The precursor is calcined and crushed to obtain single crystal cobalt tetroxide.

[0035] The present invention utilizes a dispersant as a grinding medium to grind cobalt chloride and carbonate, thereby overcoming the defect that the pure solid phase method cannot fully and evenly mix the raw materials; at the same time, the solid particles in the slurry have a small particle size and high activity after grinding, thus providing better raw materials for spray drying.

[0036] The spray drying method is adopted to make it easier for the slurry to form uniform powder during the drying process. At the same time, the spray drying process ensures that the refined particles do not agglomerate during the drying process, maintaining uniformity and dispersion. The combination of grinding and spray drying methods can obtain a precursor powder with high uniformity and small particle size distribution. At the same time, the polyhedral content of the cobalt tetroxide obtained after calcination of the precursor prepared by the grinding method and the spray drying method is relatively high. In some embodiments, the molar concentration of the cobalt chloride is 2-3 mol / L, and the molar concentration of the carbonate is 4-6 mol / L.

[0037] During the calcination process, the chloride ions of cobalt chloride will be adsorbed on the (111) plane, thereby changing the crystal growth process and making the (400) plane of some crystal particles grow faster. The resulting single crystal cobalt oxide is polyhedral or octahedral, and its (111) plane diffraction peak intensity I(111) and (400) plane diffraction peak intensity I(400) satisfy: 1.10≤I(111) / I(400)≤1.30.

[0038] In some embodiments, a precursor with high uniformity and small particle size distribution forms single-crystal cobalt oxide with small particle size, narrow particle size distribution, high particle size uniformity, high powder tap density and large specific surface area after calcination.

[0039] In some embodiments, the method for preparing single crystal cobalt oxide is characterized in that: The dispersant includes at least one of water and ethanol; And / or, the grinding method includes at least one of vertical ball milling, ultrasonic grinding and high-speed dispersion.

[0040] In some embodiments, the molar concentration ratio of cobalt chloride to carbonate is 1:2-3; And / or, the mass ratio of the total mass of the cobalt chloride and the carbonate to the mass of water is 10%-30%.

[0041] In some embodiments, during the spray drying, the feed flow rate is 2-5 L / h; and / or, the atomization frequency is 380-400 Hz; and / or, the induced air frequency is 35-40 Hz; And / or, the atomizing nozzle is a two-fluid nozzle, and the ratio of the air flow speed to the feed speed is controlled to be 0.1-10.

[0042] and / or, the air inlet temperature is 260-300°C, the air outlet temperature is 100-150°C, In some embodiments, the calcination temperature is 600-800°C.

[0043] Preferably, the calcination temperature is 700-750° C. and the calcination time is 8-14 h.

[0044] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0045] Please refer to the process flow chart Figure 1 The features and performance of the present invention are further described in detail below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0046] Embodiment 1: (1) Grinding: Cobalt chloride and ammonium bicarbonate were dispersed in deionized water, the mass of the cobalt chloride and ammonium bicarbonate mixture was 10% of the mass of water, the molar concentration of cobalt chloride was 2.5 mol / L, and the molar concentration of ammonium bicarbonate was 5 mol / L. The premix was put into a vertical ball mill with a ratio of premix to ball to material set at 9:1, and the ball milling time was 1.5 h at a speed of 900 rpm / min to obtain a slurry.

[0047] (2) Spray drying: The slurry is added to a spray drying tower through a peristaltic pump for drying to obtain a precursor. During the spray drying process, the feed flow rate is 2 L / h, the air inlet temperature is 280°C; the air outlet temperature is 140°C; the atomization frequency is 390 Hz; and the induced draft frequency is 36 Hz. The atomizing nozzle used is a two-fluid nozzle, and the ratio of the air flow velocity to the feed velocity is controlled to be 1.

[0048] (3) Calcination: The precursor is added into the feed bin of a rotary kiln and calcined at 720° C. in a high temperature zone for 10 h to obtain single crystal cobalt oxide.

[0049] Embodiment 2: (1) Grinding: Cobalt chloride and ammonium bicarbonate were dispersed in deionized water, the mass of the cobalt chloride and ammonium bicarbonate mixture was 20% of the mass of water, the molar concentration of cobalt chloride was 2 mol / L, and the molar concentration of ammonium bicarbonate was 4 mol / L. The premix was placed in a vertical ball mill with a ratio of premix to ball to material set at 8:1, at a speed of 800 rpm / min, and a ball milling time of 1 h to obtain a slurry.

[0050] (2) Spray drying: The slurry is added to a spray drying tower through a peristaltic pump for drying to obtain a precursor. During the spray drying process, the feed flow rate is 2 L / h, the air inlet temperature is 280°C; the air outlet temperature is 125°C; the atomization frequency is 380 Hz; and the induced draft frequency is 35 Hz. The atomizing nozzle used is a two-fluid nozzle, and the ratio of the air flow velocity to the feed velocity is controlled to be 0.1.

[0051] (3) Calcination: The precursor is added into the feed bin of a rotary kiln and calcined at 600° C. in a high temperature zone for 12 h to obtain single crystal cobalt oxide.

[0052] Embodiment 3: (1) Grinding: Cobalt chloride and ammonium carbonate were dispersed in deionized water, wherein the mass of the cobalt chloride and ammonium carbonate mixture was 30% of the mass of water, wherein the molar concentration of cobalt chloride was 3 mol / L, and the molar concentration of ammonium bicarbonate was 6 mol / L. The premix was put into a vertical ball mill with a ratio of premix to ball to material set at 10:1, and the ball milling time was 2 h at a speed of 1000 rpm / min to obtain a slurry.

[0053] (2) Spray drying: The slurry is added to a spray drying tower through a peristaltic pump for drying to obtain a precursor. During the spray drying process, the feed flow rate is 5 L / h, the air inlet temperature is 280°C; the air outlet temperature is 125°C; the atomization frequency is 400 Hz; and the induced draft frequency is 40 Hz. The atomization nozzle used is a two-fluid nozzle, and the ratio of the air flow velocity to the feed velocity is controlled to be 10.

[0054] (3) Calcination: The precursor is added into the feed bin of a rotary kiln and calcined at 800° C. in a high temperature zone for 6 h to obtain single crystal cobalt oxide.

[0055] Comparative Example 1: (1) Grinding: Cobalt chloride and ammonium bicarbonate were dispersed in deionized water, the mass of the cobalt chloride and ammonium bicarbonate mixture was 10% of the mass of water, the molar concentration of cobalt chloride was 2.5 mol / L, and the molar concentration of ammonium bicarbonate was 5 mol / L. The premix was placed in a vertical ball mill with a ratio of premix to ball to material set at 9:1, at a speed of 900 rpm / min, and the ball milling time was 1.5 h to obtain a slurry.

[0056] (2) Oven drying: The slurry was added to an oven via a peristaltic pump and dried at 80° C. for 12 h to obtain a precursor.

[0057] (3) Calcination: The precursor is added into the feed bin of a rotary kiln and calcined at 720° C. in a high temperature zone for 10 h to obtain single crystal cobalt oxide.

[0058] Comparative Example 2: (1) Slurry preparation: Cobalt chloride and ammonium bicarbonate are dispersed in deionized water. The mass of the mixture of cobalt chloride and ammonium bicarbonate is 10% of the mass of water. The molar concentration of cobalt chloride is 2.5 mol / L, and the molar concentration of ammonium bicarbonate is 5 mol / L.

[0059] (2) Spray drying: adding the premix to a spray drying tower through a peristaltic pump for drying to obtain a precursor. During the spray drying process, the feed flow rate is 1.5 L / h, the air inlet temperature is 280°C; the air outlet temperature is 125°C; the atomization frequency is 390 Hz; and the induced draft frequency is 36 Hz. The atomizing nozzle used is a two-fluid nozzle, and the ratio of the air flow velocity to the feed velocity is controlled to be 1.

[0060] (3) Calcination: The precursor is added into the feed bin of a rotary kiln and calcined at 720° C. in a high temperature zone for 10 h to obtain single crystal cobalt oxide.

[0061] Comparative Example 3: The difference between this comparative example and Example 1 is that in the grinding process of step (1), "cobalt chloride" is replaced by "cobalt hydroxide", and the other conditions and parameters are exactly the same as those of Example 1.

[0062] Test Example 1: The morphology and composition of the cobalt tetroxide materials obtained in Examples 1-3 and Comparative Examples 1-2 were detected by scanning electron microscopy and XRD, respectively.

[0063] Figure 2 a and Figure 2 b is the SEM images of the precursor prepared in Example 1 at different magnifications; Figure 6 a and Figure 6 b is the SEM image of the precursor prepared in Comparative Example 1 at different magnifications; Fig.10 a and Fig.10 b is the SEM image of the precursor prepared in Comparative Example 2 at different magnifications. Figure 2 a and Figure 2 b It can be seen that the precursor obtained by grinding and spray drying is a spherical agglomerate with high sphericity, small particle size and highly consistent morphology. Figure 6 a and Figure 6 b It can be seen that the precursor obtained by grinding and ordinary oven drying is an irregular agglomerate, which has large particle agglomerations. Fig.10 a and Fig.10 b It can be seen that the precursor obtained only by spray drying method is agglomerates of mixed large and small particles, and the particle size uniformity of the agglomerates is poor and the sphericity is low.

[0064] Figure 3 The XRD pattern of the precursor prepared in Example 1; Figure 7 The XRD pattern of the precursor prepared in Comparative Example 1; Fig.11 The XRD pattern of the precursor prepared in Comparative Example 2 is shown in FIG. Figure 3 It can be seen that the main components of the precursor prepared by grinding and spray drying are cobalt carbonate and cobalt chloride, and the crystallinity is relatively high. Figure 7 It can be seen that the precursor obtained by grinding and ordinary drying methods cannot identify the specific phase and has poor crystallinity, which may be cobalt carbonate or other compounds. Fig.11 It can be seen that the precursor components obtained only by spray drying are mainly cobalt carbonate and cobalt chloride, but the crystallinity is low.

[0065] Figure 4 a and Figure 4 b is the SEM images of the single crystal cobalt oxide prepared in Example 1 at different magnifications; Figure 8 a and Figure 8 b is the SEM images of the single crystal cobalt oxide prepared in Comparative Example 1 at different magnifications; Fig.12 a and Fig.12 b is the SEM image of the single crystal cobalt oxide prepared in Comparative Example 2 at different magnifications. Figure 4 a and Figure 4 b It can be seen that the single crystal cobalt oxide obtained after calcination exhibits significant polyhedral characteristics and contains octahedral particles. The particles are evenly distributed and have regular morphology, which helps to improve the tap density of the material. Figure 8 a and Figure 8b It can be seen that the single crystal cobalt oxide particles obtained after calcination from the precursor obtained by grinding and ordinary drying are unevenly distributed and severely agglomerated. The primary particle packing density is large, which is not conducive to the electrolyte wetting the inside of the positive electrode material made from this material, and is not conducive to the migration of lithium ions during the charge and discharge process, resulting in greater polarization during the charge and discharge process, thereby affecting the electrochemical performance of the battery material. Fig.12 a and Fig.12 b It can be seen that the single crystal cobalt tetroxide obtained after calcination from the precursor obtained only by spray drying still has large particle agglomerations.

[0066] Figure 5 The XRD pattern of the single crystal cobalt oxide prepared in Example 1; Fig. 9 The XRD pattern of the single crystal cobalt oxide prepared in Comparative Example 1; Fig.13 The XRD pattern of the single crystal cobalt oxide prepared in Comparative Example 2 is shown in FIG. Figure 5 It can be seen that the single crystal cobalt oxide obtained by the preparation method of the present invention has high crystallinity. Fig. 9 It can be seen that the XRD diffraction angle moves to the right, indicating that the interlayer spacing becomes smaller; other impurity elements enter the cobalt lattice and replace the cobalt position, resulting in a smaller interlayer spacing, which may cause structural deformation. Fig.13 It can be seen that the single crystal cobalt tetroxide phase obtained by the spray drying method is also a pure cobalt tetroxide phase and has a strong crystallinity.

[0067] In summary, it is shown that the combination of the grinding and spray drying methods used in the present invention plays an important synergistic role, improves the performance of the precursor and the uniformity of the material, and finally obtains single-crystal cobalt tetroxide with a narrow particle size distribution range, large tap density and specific surface area, and a polyhedral morphology and high crystallinity.

[0068] Test Example 2: The particle size distribution, tap density, specific surface area and percentage of octahedral particles of the cobalt oxide materials obtained in Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.

[0069] Among them, the particle size distribution detection method: LPS wet test, the test results, D v10 Indicates that the volume of particles smaller than or equal to this particle size accounts for 10%, D v50 It is the median of the volume distribution, indicating that the volume of particles smaller than or equal to this particle size accounts for 50%, D v90 Indicates that the volume of particles less than or equal to this particle size accounts for 90%; the particle size distribution width span satisfies: span = ; Tap density testing method: Tap density meter; Specific surface area detection method: nitrogen physical adsorption method; The test method for the percentage of octahedral particles is as follows: the SEM image of the single crystal cobalt oxide powder is analyzed, and the powder particles in the image are counted using the ImageJ image processing software; one counted particle is a primary particle with a maximum diameter ≥ 0.1 μm; the number of dispersed primary particles with octahedral morphology accounts for the number of all counted particles by the following formula, and the sample size of the counted particles is about 500: Formula = .

[0070] Table 1 Performance parameters of single crystal cobalt oxide

[0071] As can be seen from Table 1, the cobalt oxide product obtained in Example 1 has high particle size uniformity, high tap density and high specific surface area. v50 The range is 3.5-4.0; D v90 The range of is 6.0-8.0; the tap density is 2.5-3; the range of specific surface area is 0.6-0.8.

[0072] Compared with Example 1, the cobalt tetroxide obtained in Comparative Examples 1-2, which was not prepared by the combined grinding and spray drying method, had poor particle size uniformity, low tap density and low specific surface area.

[0073] Compared with Example 1, Comparative Example 3 does not use chlorine-containing cobalt salt, which cannot restrict the (111) crystal plane, making the value of I(111) / I(400) lower than 1.0.

[0074] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A single crystal cobalt oxide, characterized in that: In the X-ray diffraction spectrum of the single crystal cobalt oxide, the (111) crystal plane diffraction peak intensity I(111) and the (400) crystal plane diffraction peak intensity I(400) satisfy: 1.10≤I(111) / I(400)≤1.

30.

2. The single crystal cobalt oxide according to claim 1, characterized in that: The single crystal cobalt oxide comprises at least one of the following features 1 to 6: Feature 1: The single crystal cobalt tetroxide D v50 3.0-5.0um; Feature 2: The single crystal cobalt tetraoxide D v90 4.0-9.0um; Feature 3: The tap density of the single crystal cobalt oxide is 2.0-3.0 g / ml; Feature 4: The specific surface area of ​​the single crystal cobalt oxide is 0.6-0.8m 2 / g; Feature 5: The span of the single crystal cobalt oxide is 1.0-1.3; Feature 6: The percentage of the single-crystal cobalt oxide particles that are octahedral is 1%-10%, and the octahedron refers to a polyhedron with eight faces and six vertices.

3. A method for preparing single crystal cobalt oxide according to claim 1 or 2, characterized in that: The following steps are involved: Cobalt chloride and carbonate are dispersed in a dispersant to obtain a premix; The premix is ​​ground to obtain a slurry; The slurry is spray-dried to obtain a precursor; The precursor is calcined and crushed to obtain single crystal cobalt tetroxide.

4. The method for preparing single crystal cobalt oxide according to claim 3, characterized in that: The molar concentration ratio of the cobalt chloride to the carbonate is 1:2-3; And / or, the mass ratio of the total mass of the cobalt chloride and the carbonate to the mass of water is 10%-30%.

5. The method for preparing single crystal cobalt oxide according to claim 3, characterized in that: The dispersant includes at least one of water and ethanol; And / or, the grinding method includes at least one of vertical ball milling, ultrasonic grinding and high-speed dispersion.

6. The method for preparing single crystal cobalt oxide according to claim 3, characterized in that: When the grinding method is ball milling, the mass ratio of balls to materials in the ball mill is 8-10:1; And / or, the rotation speed of the ball mill is 800-1000 rpm / min, and the time is 1-2h.

7. The method for preparing single crystal cobalt oxide according to claim 5, characterized in that: During the spray drying, the feed flow rate is 2-5 L / h; and / or, the atomization frequency is 380-400 Hz; and / or, the induced air frequency is 35-40 Hz; And / or, the atomizing nozzle is a two-fluid nozzle, and the ratio of the air flow speed to the feed speed is controlled to be 0.1-10.

8. The method for preparing single crystal cobalt oxide according to claim 3, characterized in that: The calcination process temperature is 600-800°C.

9. A lithium cobalt oxide positive electrode material, characterized in that: The lithium cobaltate is obtained by mixing cobalt trioxide and a lithium source and then calcining them; the cobalt trioxide includes the single crystal cobalt trioxide according to any one of claims 1-2, or the single crystal cobalt trioxide obtained by the preparation method of the single crystal cobalt trioxide according to any one of claims 3-8.

10. A battery, characterized in that: The battery comprises a positive electrode sheet, and the positive electrode sheet comprises the lithium cobalt oxide positive electrode material according to claim 9.